Refugee Journeys Histories of Resettlement, Representation and Resistance - Silverstein, Jordana; Stevens, Rachel (ANU Press, 2021)
Refugee Journeys presents stories of how governments, the public and the media have responded to the arrival of people seeking asylum, and how these responses have impacted refugees and their lives. Mostly covering the period from 1970 to the present, the chapters provide readers with an understanding of the political, social and historical contexts that have brought us to the current day. This engaging collection of essays also considers possible ways to break existing policy deadlocks, encouraging readers to imagine a future where we carry vastly different ideas about refugees, government policies and national identities.